UNSTABLE CRITICAL EQUILIBRIUM IN THE DYNAMICS OF COMPLEX STRUCTURED POPULATION OF STURGEON - V. A. Dubrovskaya; T. N. Solovieva; A. Yu. Perevaryukha (Системный анализ и прикладная информатика, 2016)
The article deals with the consequences of the existence of special conditions that determine the character of the rapid further development of population processes. The most probable connection of these critical conditions deals with the optimal number of subpopulation groups. These groups are formed by the evolutionary adaptation of the form of restricted access to resources for reproduction. We have proposed a model of population processes, which formalizes the influence of uneven growth rate for two different groups of reproductive sturgeon mortality of migratory fish in the juvenile period of Acipenser gueldenstaedtii development. In the computing environment was investigated the hybrid system, which simulates the effects of the existence of the situation for the population of migrating juvenile disproportionate reduction in the river. Such cases are established by us according to the rapid decline in sturgeon spawning the Volga. For the exploited population threshold effect after the unstable equilibrium with the minimum necessary for the well being of the form number is the count in the implementation of the «collapse». The phenomenon of collapse detached among all scenarios the most valuable long-term degradation of the reproductive group. In addition to the apparent sharp reduction in reproductive performance, threshold effect is reflected in the adverse events previously dominated evolutionary trend for the survival of certain forms of the life cycle of fish in terms of reorganization of the fishery. Informative, that the Volga stellate sturgeon Acipencer stellatus observed some form of non-linearity in the efficiency of spawning and require a different kind of fish-specific mathematical model.